RANCANG BANGUN SISTEM INFORMASI PARIWISATA KOTA BATAM BERBASIS E- LAYANAN - tanjung, muhammad iqbal; Elisa, Erlin (LPPM Universitas Putera Batam, 2021)
abstrack The role of technology that develops in everyday life has many benefits, The benefits of this information technology have a long-term development impact, so that in the development of the technological age it is bound to change, information and communication technology can help facilitate people in various sectors of life, wrong one of them is the tourism sector, an area that has interesting tourist attractions to explore in Indonesia is Batam City. Batam City has tourism potential that is very interesting to explore. The special natural beauty that is still preserved makes it one of the tourist destinations that have its own charm, but unfortunately at this time tourist attractions in Batam City are still not exposed to the results of this research making tourism accessible in real time fast and accurate. The method used is waterfall with SDLC which consists of planning, analysis, planning, implementation and maintenance.